A NEW ASTROBLEME IN THE PACIFIC OCEAN - Levin B.W.; Gretskaya E.V.; Nemchenko G.S. (My University, 2006)
The ring structure in the Northwestern Pacific was discovered by Sakhalin researchers during the sea expedition carried out by the Institute of Marine Geology and Geophysics (Yuzhno-Sakhalinsk) on cruise 38 of the R/V Morskoy Geofizik in 1991. Preliminary information and possible versions of the depression nature (endogenic or cosmic) were discussed earlier as a preliminary analysis.